An Alternative Concept in Making Hybrid Flow Batteries into Dendrite-Free Full-Flow Batteries - Weng, Guo-Ming (Current Alternative Energy, 2024)
In this study, the author proposes an alternative concept of using electrostatic force of cation-exchange resin to attract metal ions and nanoscale conductors onto the polymer matrix to conduct the electrons for the plating/stripping of the metal species. Due to the even distribution of the positively-charged functional groups inside the cation-exchange resin, metal formation can also be well distributed and safety issue caused by metal dendrite can be eliminated. By applying this transformative concept, various hybrid flow batteries could be “upgraded” to dendrite-free full-flow batteries. Interestingly, this new concept could also be generalized for all metal-based aqueous and nonaqueous hybrid systems to upgrade them into next-generation full-flow battery systems. This work offers an alternative concept to deliver unprecedented battery systems and the proof-of-concept would be more easily implemented than anticipated.
Keywords: cation-exchange resin